Does vitamin D supplementation alter plasma adipokines concentrations? A systematic review and meta-analysis of randomized controlled trials. (May 2016) - Dinca, Madalina; Serban, Maria-Corina; Sahebkar, Amirhossein; Mikhailidis, Dimitri P.; Toth, Peter P.; Martin, Seth S.; Blaha, Michael J.; Blüher, Matthias; Gurban, Camelia; Penson, Peter; Michos, Erin D.; Hernandez, Adrian V.; et al.
Graphical abstract: Forest plot displaying mean difference and 95%CI for the impact of vitamin D supplementation on plasma adiponectin concentrations. Abstract: We aimed to elucidate the role of vitamin D supplementation on adipokines through a systematic review and a meta-analysis of randomized placebo-controlled trials (RCTs). The search included PUBMED, Scopus, Web of Science and Google Scholar through July 1st, 2015. Finally we identified 9 RCTs and 484 participants. Meta-analysis of data from 7 studies did not find a significant change in plasma adiponectin concentrations following vitamin D supplementation (mean difference [MD]: 4.45%, 95%CI: ⿿3.04, 11.93, p = 0.244; Q = 2.18, I 2 = 0%). In meta-regression, changes in plasma adiponectin concentrations following vitamin D supplementation were found to be independent of treatment duration (slope: 0.25; 95%CI: ⿿0.69, 1.19; p = 0.603) and changes in serum 25-hydroxy vitamin D [25(OH)D] levels (slope: ⿿0.02; 95%CI: ⿿0.15, 0.12; p = 0.780). Meta-analysis of data from 6 studies did not find a significant change in plasma leptin concentrations following vitamin D supplementation (MD: ⿿4.51%, 95%CI: ⿿25.13, 16.11, p = 0.668; Q = 6.41, I 2 = 21.97%). Sensitivity analysis showed that this effect size is sensitive to one of the studies; removing it resulted in a significant reduction in plasma leptin levels (MD: ⿿12.81%, 95%CI: ⿿24.33, ⿿1.30, p = 0.029). In meta-regression, changes in plasma leptin concentrations following vitamin D supplementation were found to be independent of treatment duration (slope: ⿿1.93; 95%CI: ⿿4.08, 0.23; p = 0.080). However, changes in serum 25(OH)D were found to be significantly associated with changes in plasma leptin levels following vitamin D supplementation (slope: 1.05; 95%CI: 0.08, 2.02; p = 0.033). In conclusion, current data did not indicate a significant effect of vitamin D supplementation on adiponectin and leptin levels.